2020
DOI: 10.34172/aim.2020.61
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Management during the COVID-19 Pandemic: An Iranian Expert Opinion Statement

Abstract: The coronavirus infection is an evolving pandemic with high morbidity and mortality, especially in people with comorbidities. The case fatality rate (CFR) is 9.2% in the presence of diabetes, while it is 1.4% in those without any comorbidity. Diabetes is a prevalent disease globally; hence, healthcare professionals are highly concerned about severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic progression. Current evidence does not support higher incidence of coronavirus disease 2019 (COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It is also important to take enough proteins in their diet and avoid smoking because it could exacerbate the corona virus infection. Patients with diabetes also tend to reduce their meetings with their doctor to avoid exposure to COVID-19 but this could lead to the mismanagement of their disease and uncontrolled hyper or hypoglycemia so the health care system need to develop new policies for telehealth services to provide support and care to diabetic patients during this pandemic safely [ 103 ]. Impact of Diabetes treatment on COVID-19 outcome …”
Section: Introduction To Covid-19 and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to take enough proteins in their diet and avoid smoking because it could exacerbate the corona virus infection. Patients with diabetes also tend to reduce their meetings with their doctor to avoid exposure to COVID-19 but this could lead to the mismanagement of their disease and uncontrolled hyper or hypoglycemia so the health care system need to develop new policies for telehealth services to provide support and care to diabetic patients during this pandemic safely [ 103 ]. Impact of Diabetes treatment on COVID-19 outcome …”
Section: Introduction To Covid-19 and Diabetesmentioning
confidence: 99%
“…The last matter addressed in the present research is the management of diabetes during this pandemic. Studies suggest that diabetic patients should follow their antidiabetic drugs as prescribed, have routine aerobic activities, control their glycemic indexes in their diet and check their blood sugar to make sure their diabetes is under control and should stay in touch with their physicians by telephone or over the internet to help them be safe and healthy during the pandemic [ 103 ]. Introduction to COVID-19 and Dyslipidemia …”
Section: Introduction To Covid-19 and Diabetesmentioning
confidence: 99%
“…One essential solution for effectively controlling the imposed burden of DM during the COVID-19 pandemic could be applying telemedicine and telehealth services [ 100 ]. Policymakers should pave the wave to ensure that patients with DM could still access essential care during the ongoing waves of the pandemic [ 101 ]. In addition, intensified glycemic control is recommended in those with both COVID-19 and DM [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although diabetes is prevalent worldwide, healthcare professionals are worried about this new pandemic's consequences regarding diabetes [4]. While it has been shown that persons with diabetes (PWD) are considered as high risk population for developing complications [5]; herein, we presented a young patient with new onset diabetes after SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 98%